PWE-370 Colonoscopy comfort and subsequent faecal occult blood screening uptakein the english bowel cancer screening programme. (22nd June 2015) - Lo, SH; Ghanouni, A; Rees, C; Rutter, M; Snowball, J; Seaman, H; Halloran, S; Wardle, J; von Wagner, C
Abstract : Introduction: Abnormal guaiac Faecal Occult Blood test (gFOBt) screening results are associated with lower subsequent screening uptake among individuals who are referred back for routine screening (Lo et al . 2015). Negative experience with a colonoscopy prompted by a positive gFOBt may contribute to an individual's decision not to repeat screening. This study examined the association between nurse-reported colonoscopy discomfort on subsequent gFOBt screening uptake in the NHS Bowel Cancer Screening Programme (BCSP). Method: gFOBt uptake of three screening invitation rounds (R1-R3) was recorded for 322, 791 individuals aged 60–64 at the time of the first gFOBt screening invitation and living within the catchment area of the Southern Hub of the NHS BCSP. Nurse-reported colonoscopy discomfort scores (no/ minimal/ mild/ moderate/ severe) from a previous episode (R1 or R2) were used to predict repeat gFOBt uptake in R2 and R3 among individuals who remained eligible for routine screening. 1, 566 out of 2, 489 (63%) individuals who had undergone a colonoscopy in R1 remained eligible for screening in R2. 1, 444 out of 5, 720 (25%) individuals who had undergone a first colonoscopy in R1 or R2 were eligible for screening in R3. Nurse-reported colonoscopy discomfort scores were recorded for 1, 495 out of 1, 566 (95%) individuals who were invited for repeat gFOBt screening in R2 and 1, 366 out of 1, 444 (95%) who were invited for repeat screening in R3. Discomfort scores from second and further colonoscopies were excluded from the analysis, as they were only available for a very small number of patients (n ≤ 44). Results: Discomfort during the first colonoscopy examination was not associated with subsequent gFOBt screening uptake in R2 (OR = 0.97, 95% CI: 0.84 – 1.11, p = 0.63) or R3 (OR = 0.96, 95% CI: 0.82 – 1.14, p = 0.67). There was, however, evidence of a negative association between discomfort during recovery after the first examination and subsequent gFOBt uptake in R2 (OR = 0.74, 95% CI: 0.56 – 0.99, p = 0.04) and in R3 (OR = 0.66, 95% CI: 0.43 – 1.02, p = 0.06). Conclusion: Discomfort during a first colonoscopy examination did not appear to be associated with reduced subsequent gFOBt screening uptake, although discomfort during recovery was associated with lower subsequent uptake. Future research should repeat this analysis in a national sample and include adherence to surveillance as an additional outcome for people with intermediate- and high-risk adenomas detected at colonoscopy. Disclosure of interest: None Declared.